1996
DOI: 10.1111/j.1365-2044.1996.tb12558.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anaesthesia with midazolam and a target‐controlled propofol infusion

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
(5 reference statements)
0
14
0
1
Order By: Relevance
“…DeLucia & White [7] studied a combination of fentanyl, midazolam and propofol and recorded a significantly greater decrease in mean arterial pressure during induction when midazolam 2 mg was used. However, other studies have found no statistically significant differences in arterial pressure between groups receiving midazolam and propofol or propofol alone [2,4,11]. It therefore seems that, although the addition of midazolam reduces the propofol dose requirements significantly, it does not necessarily lead to better maintenance of arterial blood pressure during induction and may cause a transiently lower decrease in systolic and mean pressures.…”
Section: Discussionmentioning
confidence: 92%
“…DeLucia & White [7] studied a combination of fentanyl, midazolam and propofol and recorded a significantly greater decrease in mean arterial pressure during induction when midazolam 2 mg was used. However, other studies have found no statistically significant differences in arterial pressure between groups receiving midazolam and propofol or propofol alone [2,4,11]. It therefore seems that, although the addition of midazolam reduces the propofol dose requirements significantly, it does not necessarily lead to better maintenance of arterial blood pressure during induction and may cause a transiently lower decrease in systolic and mean pressures.…”
Section: Discussionmentioning
confidence: 92%
“…[14][15][16][17] Therefore, benzodiazepine reduces propofol requirements probably due to its synergistic action on GABA A -receptor. 3,7,8 Although we maintained the same sedation level in all groups, fewer patients in Group-DZ recalled intraoperative events than in other groups. Benzodiazepines, including diazepam, produce anterograde amnesia, and this may contribute to this reduction of the memories of intraoperative events.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, benzodiazepines and propofol act synergistically. 3,7,8 It is possible that preanesthetic diazepam reduces the propofol requirements and decreases the complications. Both drugs are useful for premedication, however, there are few reports to investigate the differences between them when used as premedicants for sedation with propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Oxorn et al (1997) did not observe any significant effect of midazolam on the propofol requirement whereas others have demonstrated an approximate 50% reduction in propofol dose for induction of anaesthesia if midazolam is given up to 10 minutes prior to propofol administration (Short & Chui 1991;Ong et al 2000). Premedication with midazolam also increased the number of human patients achieving successful induction of general anaesthesia with a fixed low target of PTCI without major cardiovascular effects (Tzabar et al 1996). In dogs, however, midazolam administered as an intramuscular (IM) premedication or intravenous (IV) co-induction agent, at doses of 0.1 and 0.2 mg kg À1 respectively, resulted in excitement and only a mild reduction in propofol requirement for induction of anaesthesia (Stegmann & Bester 2001;Covey-Crump & Murison 2008;Hopkins et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Premedication with midazolam also increased the number of human patients achieving successful induction of general anaesthesia with a fixed low target of PTCI without major cardiovascular effects (Tzabar et al. ). In dogs, however, midazolam administered as an intramuscular (IM) premedication or intravenous (IV) co‐induction agent, at doses of 0.1 and 0.2 mg kg −1 respectively, resulted in excitement and only a mild reduction in propofol requirement for induction of anaesthesia (Stegmann & Bester ; Covey‐Crump & Murison ; Hopkins et al.…”
Section: Introductionmentioning
confidence: 99%